Flying Seguras - Jim Keith (Coy C. Carpenter Library, 1959)
Published in: Baptist Hospital Topics. v.4, n.1. April 1959. p.4.
North Carolina Baptist Hospital patient Carmen Segura is shown here in 1959 with a make-up box primping and getting ready to leave the hospital. Ringling Brothers and Barnum and Bailey Circus hired Segura and her family from Spain as trapeze artists in 1958. Carmen's special act was to swing high above a crowd suspended by her feet. In 1959 at the circus show in Charlotte, NC she was accidently injured by a blow to the head with a swinging trapeze. Persistent headaches troubled her and by the time the circus had finished in Charlotte and had arrived in Winston-Salem, Carmen decided it would be best to enter NCBH for observation. She was found to be okay and much to her surprise and pleasure she met medical students, their wives and a hospital secretary that spoke her native language of Spanish. This made communicating easier because Carmen did not speak English.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth